Seeding diversity : enhancing farmers’ access to crop varieties and quality planting materials in Uganda’s seed systems - Mulesa, Teshome Hunduma; Otieno, Gloria; Dalle, Paule Sarah; Mubiru, Daudi Mohamed; Westengen, Ola Tveitereid (2024)
Ensuring food and livelihood security in rural areas relies heavily on crop diversity, yet farmers often struggle to access suitable seeds and planting materials. This study maps and characterizes Uganda’s seed systems to identify approaches to enhance farmers’ access to seeds of well-adapted and preferred varieties. Based on qualitative data from key informant interviews (KIIs) with a range of actors involved in the seed system, focus group discussions (FGDs) with women and men farmers, document analysis, and stakeholder workshops, this report examines the country’s seed systems from the local to the national level focusing on key seed system functions and outcomes